Mutations within DR2 independently reduce the amount of both minus- and plus-strand DNA synthesized during duck hepatitis B virus replication. - Loeb, D D (1996)
The initial aim of this study was to examine the role of complementarity between the plus-strand primer and the minus-strand DNA template for translocation of the plus-strand primer in hepadnaviral replication. We show that when a 5-nucleotide substitution was placed in either DR1 or DR2, translocation of the primer at a detectable level did not occur. Placing the mutation in both DR1 and DR2 did not restore primer translocation, which indicates that complementarity is not the sole determinant for primer translocation. These mutants, in which primer translocation has been inhibited, have been additionally informative. The mutation in DR1 led to efficient synthesis of plus-strand DNA, albeit primed in situ. In contrast, the mutation in DR2 resulted in a reduction in the amount of plus-strand DNA synthesized per unit of minus-strand DNA. These findings were interpreted as indicating that a mutation at DR2, the primer acceptor site, can inhibit both primer translocation and in situ priming. Lastly, we show that mutations within DR2 can result in a reduction in the synthesis of minus-strand DNA and that this reduction is occurring at an early phase of the process. We speculate that this reduction in the amount of minus-strand DNA synthesized could be due to an inhibition of the template switch during minus-strand DNA synthesis.